Relation between the grafting density of liquid crystal macromolecule and the symmetry of self-assembled bulk phase: coarse-grained molecular dynamics study - Ilnytskyi, J.M. (Condensed Matter Physics, 2013)
I consider a generic coarse-grained model suitable for the study of bulk self-assembly of liquid crystal (LC) macromolecules. The cases include LC dendrimers, gold nanoparticles modified by polymer chains with terminating LC groups and oth. The study is focused on the relation between a number of grafted chains, Nch, and the symmetry of the self-assembled bulk phases. Simple space-filling arguments are used first to estimate stability intervals for a rod-like, disc-like and spherulitic conformations in terms of Nch. These are followed by coarse-grained molecular dynamics simulations for both spontaneous and aided self-assembly of LC macromolecules into bulk phases. In spontaneous self-assembly runs, essential coexistence of rod-like and disc-like conformations is observed (via analysis of the histograms for the molecular asphericity) in a broad interval of Nch, which prevents formation of defect-free structures. The use of uniaxial and planar aiding fields is found to improve self-assembly into monodomain phases by promoting conformations of respective symmetry. Strong shape-phase relation, observed experimentally, is indicated also by the simulations by the coincidence of the stability intervals for the respective conformations with those for the bulk phases. Розглянуто узагальнену модель, придатну для опису об’ємного впорядкування рiдкокристалiчних (РК) макромолекул (наприклад, РК дендримерiв; наночастинок золота, модифiкованих полiмерними ланцюжками iз кiнцевими РК групами тощо). Дослiдження концентрується на взаємозв’язку мiж кiлькiстю приєднаних ланцюжкiв N
ch
та симетрiєю впорядкованої фази. Використовуючи простi геометричнi обчислення спочатку оцiнено iнтервали стабiльностi для стержне-, диско- та сферо-подiбних молекулярних конформацiй залежно вiд N
ch
. Далi виконано моделювання за допомогою молекулярної динамiки для спонтанного та керованого самовпорядкування РК макромолекул в об’ємнi фази. Пiд час спонтанного самовпорядкування шляхом аналiзу гiстограм для молекулярної асферичностi виявлено спiвiснування стержне-та дископодiбних конформацiй в широкому iнтервалi N
ch
, що перешкоджає формуванню бездефектних структур. Використання одновiсного або планарного керуючих полiв суттєво покращує самовпорядкування вiдповiдних монодоменних фаз шляхом селекцiї конформацiй з вiдповiдною симетрiєю. Сильна залежнiсть мiж формою молекули та симетрiєю фази, яка спостерiгається експериментально, також виявляється i при моделюваннi – через спiвпадiння iнтервалiв стабiльностi вiдповiдних конформацiй та об’ємних фаз.